Phlegmonous Gastritis Following Coronary Bypass Surgery - J Radhi; M Kamouna; J Nyssen (Canadian Journal of Gastroenterology, 1999)
Phlegmonous gastritis is a rare, rapidly progressive and potentially fatal gastric bacterial infection. A case of phlegmonous gastritis following a coronary bypass surgery is described. This condition was not diagnosed premortem due to the nonspecific nature of the gastrointestinal symptoms. Upper gastrointestinal endoscopy may be of value in establishing the diagnosis in emergencies with culture of gastric aspirate and biopsy.